Evaluation of the Quality and Accessibility of Available Websites on Kidney Transplantation - Valizadeh-Haghi, Saeideh; Rahmatizadeh, Shahabedin (Urology Journal, 2018)
Purpose: (i) to assess the quality of health websites on kidney transplant and (ii) to evaluate the accessibility of these websites and their concordance with the existing guidelines. Materials and Methods: The terms “kidney transplantation” and “renal transplantation” were searched in the three most popular search engines Google, Yahoo, and Bing. 58 unique websites were eligible for the analysis . The Websites accessibility was evaluated using the AChecker tool. Kruskal–Wallis test was performed to examine any significant difference between accessibility issues across different domains. The eligible websites were screened for quality based on the HONcode of conducts. Moreover, the daily traffic data of each website was determined by Alexa. The correlation of known accessibility problems with website popularity was examined too. Result: The main reported known problems belonged to “scripts must have functional text,” “text equivalents,” “accessible forms,” and “text links for server-side image map”. Although the mean accessibility errors in governmental (10.25 ± 7.274) and organizational (12.31 ± 9.469) websites were less than those in the other domains, the differences were not significant (P = 0.60). Findings showed no significant correlation (P > 0.05) between the extent of known problems (16.50 ± 12.18) and Alexa ranking (253675.07 ± 534690.947). Furthermore, most websites on kidney transplant were not certified by the HONcode. Conclusion: The health websites designers should be aware of accessibility problems, because there is a growing population of potential users with disabilities. This study indicated the need to ensure the compliance of kidney transplant websites with accessibility guidelines such as Section 508. Furthermore, most surveyed websites were of poor quality and unreliable. Therefore, physicians should warn their patients about unqualified online health information and guide them to websites which are more reliable.